Breaking the Rule of Cool : Interviewing and Reading Women Beat Writers - Grace, Nancy McCampbell (Book collections on Project MUSE., 2012)
BIOGRAPHY ̈LITERARY CRITICISM-- & The Beat movement nurtured many female dissidents and artists who contributed to Beat culture and connected the Beats with the second wave of the women's movement. Although they have often been eclipsed by the men of the Beat Generation, the women's contributions to Beat literature are considerable. Covering writers from the beginning of the movement in the 1950s and extending to the present, this book features interviews with nine of the best-known women Beat writers, including Diane di Prima, ruth weiss, Joyce Johnson, Hettie Jones, Joanne Kyger, Brenda Fraz.